Veintisiete años de seguimiento de las clínicas integrales de la Facultad de Odontología de la Universidad de Antioquia (1970-1996)- parte II- evaluación del período 1970- 1989 - Mejía-Villa, Raúl; Yepes-Delgado, Fanny Lucía (Revista Facultad de Odontología Universidad de Antioquia, 2017)
This dental Clinics Evaluation was done based on a retrospective study of the patients dental charts. From a 356 total charts, a sample of 102 was studied, representative to a 98% confidence level. This research allows to identify the integrated dental clinics as a clinical method for teaching, which presented serious limitations in the studied period in some positions or qualitative teaching aspects, and in the evaluation of the 'structure", "the process" and the "results" as constitutive elements of the "quality" in a health service. Several suggestions of support political-administrative, were presented in order to improve the teaching area, and the dental health service of the clinics.